A New Radiologic Protocol and a New Occlusal Radiographic Index for Computer-Guided Implant Surgery. Issue 5 (July 2016) - De Santis, Daniele; Graziani, Pierfrancesco; Castellani, Roberto; Zanotti, Guglielmo; Gelpi, Federico; Marconcini, Simone; Bertossi, Dario; Nocini, Pier Francesco
Abstract : Abstract: A minimum interarch space of 40 mm along the planned direction of the implant is physically mandatory to allow computer-guided implant placement with the NobelGuide technique. The aim of this paper was to describe a novel radiologic protocol and a new occlusal radiographic index that give the clinician the possibility of identifying patients with limited interarch space. Three patients undergoing NobelGuide treatment of the edentulous upper jaw were selected as candidates for this study. In the first patient, the radiographic occlusal index was built using an addition silicone material to occupy the space between the 2 arches forced into the maximum opening position. In the other 2 patients different silicone materials were used and 2 interpositional wedges were placed in between 2 silicone bites to ensure maximum mouth opening. In the first patient, the bite made with addition silicone alone resulted in distinct noise on computer tomography since the patient was not forced to achieve his maximum opening position. In the second patient the mandibular addition silicone was still quite visible, while in the third patient the condensation silicone was invisible and the quality of the image was excellent with the possibility of measuring maximum opening position and virtually predicting interference with the opposite arch. The new radiological occlusal index made with condensation silicone (Sandwich Index) proved to be effective in reproducing the maxillary forced maximum opening position during the initial planning phase, preventing errors in the inclusion or exclusion of patients suitable for NobelGuide treatment.